2019
DOI: 10.1093/infdis/jiz532
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of the Broadly Neutralizing Human Immunodeficiency Virus (HIV)-1 Monoclonal Antibody VRC01 in HIV-Exposed Newborn Infants

Abstract: Background While mother-to-child HIV transmission has dramatically decreased with maternal antiretroviral therapy, breast milk transmission accounts for most of the 180,000 new infant HIV infections annually. Broadly neutralizing antibodies (bNAb) may further reduce transmission. Methods A Phase I safety and pharmacokinetic study was conducted: a single subcutaneous (SC) dose of 20 or 40 mg/kg (Dose Groups 1 and 2, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…Similar in intent and yet different in approach to bNAbs, engineered antibody-like entry inhibitor molecules (eCD4-Ig) that simultaneously emulate both the target CD4 receptor and a coreceptor, CXCR4 or CCR5, have demonstrated a capacity for high neutralization breadth and a lower potential for viral escape than a single bNAb (35). In contrast to the concerns associated with the administration of single bNAb as a maternal intervention, a recent phase I study has demonstrated the safety, tolerability, and pharmacokinetics of passive administration of VRC01-LS bNAb in HIV-exposed infants as adjunctive therapy to ART to further reduce postnatal transmission via breastfeeding (36). Thus, while development of a safe and highly effective maternal HIV vaccine remains elusive, passive immunization strategies may be used to complement existing maternal and infant ART regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Similar in intent and yet different in approach to bNAbs, engineered antibody-like entry inhibitor molecules (eCD4-Ig) that simultaneously emulate both the target CD4 receptor and a coreceptor, CXCR4 or CCR5, have demonstrated a capacity for high neutralization breadth and a lower potential for viral escape than a single bNAb (35). In contrast to the concerns associated with the administration of single bNAb as a maternal intervention, a recent phase I study has demonstrated the safety, tolerability, and pharmacokinetics of passive administration of VRC01-LS bNAb in HIV-exposed infants as adjunctive therapy to ART to further reduce postnatal transmission via breastfeeding (36). Thus, while development of a safe and highly effective maternal HIV vaccine remains elusive, passive immunization strategies may be used to complement existing maternal and infant ART regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I studies showed VRC01 to be safe and well tolerated without dose-associated toxicity or serious adverse effects in healthy adults and HIV-exposed infants [6,25]. Its long-term clinical and functional activities have also been examined in healthy humans.…”
Section: Efficacy Of Next-generation Bnabs In Clinical Trialsmentioning
confidence: 99%
“…VRC01, VRC01LS and VRC07-523LS were administered subcutaneously to HIV-exposed infants. VRC01 demonstrated a good safety profile when administered as either a single dose or in multiple doses [55].…”
Section: Subcutaneous Injection Of Antibodymentioning
confidence: 99%